Konsepsi Pembinaan Baca-Tulis Al-Qur’an - Sri Mawaddah (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
The term "Baca" contains two substances, namely: recitations and qira'ah. The term recitation contains the meaning of following (reading) as it is both physically and following the trail and wisdom or reading as it is in accordance with the rules of correct and good reading. Qiraah also contains the meaning of conveying, studying, reading, researching, studying, exploring, knowing the characteristics, or reflecting on readings that do not have to be written texts. Write means to make letters (numbers) with a pen (pencil) or chalk. Understanding the Qur'an cannot be separated from the habit of reciting it (reading) and writing it down (writing). In terms of learning, reading, and writing the Qur'an is an effort to maintain Allah's revelation that has been revealed to the Prophet Muhammad as a guide for human life. It is very important to pay attention to the next generation because the generation that is able to read and write the Qur'an includes its maintenance (al-Qur'an). It takes a conception that can be a guide in learning to read and write the Qur'an.